Effect of Growth Stage on Essential‐Oil Yield and Composition of Daucus sahariensis. Issue 11 (November 2013) - Flamini, Guido; Smaili, Tahar; Zellagui, Amar; Gherraf, Noureddine; Cioni, Pier Luigi
Abstract The essential oils obtained by hydrodistillation from Daucus sahariensisMurb. harvested at three different growth stages were characterized by GC/MS analysis. In total, 88 compounds were identified, with myristicin (29.8–51.7%), myrcene (6.7–31.1%), α‐pinene (11.6–14.8%), and limonene (5.3–11.5%) as main constituents. Monoterpene hydrocarbons were the most represented compounds in the oils of the plant samples collected during the flower‐budding and full‐flowering periods. On the contrary, during the fruiting stage, the oils were dominated by phenylpropanoids. The essential oils were subject of considerable variation in their composition during the various developmental stages, particularly concerning the content of myrcene that decreased significantly passing from the vegetative to the fruiting stage. Conversely, for myristicin, the opposite trend was observed. Furthermore, the essential‐oil yields were quite low during the flower‐budding phase (0.27%), but rapidly increased during plant development (0.63 and 0.68% for the flowering and fruiting phases, resp.).